Inkonsistensi Peraturan Perundang-Undangan Dalam Praktik Penyelenggaraan Pemerintahan Daerah Di Indonesia - Luluk Imro'atus Sholikah; Lutfiya Yuni Rahmawati (El-Dusturie, 2025)
Abstract: This research is motivated by the problem of disharmony and overlapping legislation that affects the effectiveness of regional governance in Indonesia. Although the regional government system has undergone various reforms since the post-reform era and is regulated under Law No. 23 of 2014, inconsistencies between central and regional regulations, as well as among sectoral laws, continue to occur in practice. The study addresses two main research questions: (1) what are the forms of inconsistency found in the implementation of laws and regulations in regional governance, and (2) how do these inconsistencies impact the effectiveness of local government administration and what efforts can be taken to resolve them. This study applies a normative legal research method using a statute approach, analyzing various laws, legal documents, and relevant academic literature. The findings reveal five key areas of inconsistency: the distribution of authority between central and regional governments, the application of legal norms, financial arrangements, law enforcement, and mechanisms of supervision and guidance. These inconsistencies lead to legal uncertainty, overlapping authority, weak accountability, and declining public trust in government institutions. The study recommends comprehensive legal harmonization, stronger oversight mechanisms, increased legal awareness among bureaucrats, and systemic legislative reform to achieve alignment between sectoral and regional regulations. Therefore, regulatory consistency is a fundamental prerequisite for realizing the rule of law and ensuring the effectiveness of regional autonomy in Indonesia. Keywords: inconsistency, legislation, regional governance, harmonization, autonomy